The Role of Verbal and Visual Text in the Process of Institutionalization - Meyer, Renate E.; Jancsary, Dennis; Höllerer, Markus A.; Boxenbaum, Eva (Academy of Management Review, 2018)
In this article we develop novel theory on the differentiated impact of verbal and visual text on the emergence, rise, establishment, and consolidation of institutions. Integrating key insights from social semiotics into a discursive model of institutionalization, we identify distinct affordances of verbal and visual text based on the constitutive features of these semiotic modes. In an effort to extend scholarly inquiry into the relationship of text and institutions, we develop a set of propositions on how and under which conditions verbal and visual text, respectively, facilitate the institutionalization of novel ideas in each stage of the process. Our theory development has implications for research on institutions as communicative accomplishments, contributes to the nascent line of multimodal research, and provides novel insights into institutional emergence.